(untitled) (Semiárida, 2021)
Germination and emergence are states of the life cycle of plants that condition the success of the establishment of the species. In degraded areas of grasslands, knowing the moment of greatest emergence of forage species is an indicator of the opportune moment for the addition of native plant seeds. Piptochaetium napostaense is a grass of interest from a livestock point of view in the Caldenal area. The objective of this work was to evaluate the emergence of seedlings of the species at different sowing dates, for two consecutive years. The greatest emergence in 2017 was on the first sowing date with 82 seedlings.m2, differing from the other dates. In 2018, the maximum emergence was for the third date with 123 seedlings.m2 emerged, but it did not differ from the rest of the dates where seedling emergence was registered. Sowing dates from the end of April resulted in less seedling emergence for the evaluated years.